Monitoring of plexiform neurofibroma in children and adolescents with neurofibromatosis type 1 by [18F]FDG‐PET imaging. Is it of value in asymptomatic patients?. Issue 1 (3rd August 2017) - Azizi, Amedeo A.; Slavc, Irene; Theisen, Benjamin Emile; Rausch, Ivo; Weber, Michael; Happak, Wolfgang; Aszmann, Oskar; Hojreh, Azadeh; Peyrl, Andreas; Amann, Gabriele; Benkoe, Thomas M.; Wadsak, Wolfgang; et al.
Abstract: Purpose: About 10% of patients with neurofibromatosis type 1 (NF‐1) develop malignant peripheral nerve sheath tumours (MPNST) mostly arising in plexiform neurofibroma (PN); 15% of MPNST arise in children and adolescents. 2‐[ 18 F]fluoro‐2‐deoxy‐d‐glucose ([ 18 F]FDG)‐PET (where PET is positron emission tomography) is a sensitive method in differentiating PN and MPNST in symptomatic patients with NF‐1. This study assesses the value of [ 18 F]FDG‐PET imaging in detecting malignant transformation in symptomatic and asymptomatic children with PN. Methods: Forty‐one patients with NF‐1 and extensive PN underwent prospective [ 18 F]FDG imaging from 2003 to 2014. Thirty‐two of the patients were asymptomatic. PET data, together with histological results and clinical course were re‐evaluated retrospectively. Maximum standardised uptake values (SUVmax) and lesion‐to‐liver ratio were assessed. Results: A total of 104 examinations were performed. Mean age at first PET was 13.5 years (2.6–22.6). Eight patients had at least one malignant lesion; four of these patients were asymptomatic. Two of four symptomatic patients died, while all patients with asymptomatic malignant lesions are alive. All malignant tumours could be identified by PET imaging in both symptomatic and asymptomatic patients. All lesions judged as benign by [ 18 F]FDG imaging and clinical judgment were either histologically benign if removed or remained clinically silent during follow‐up. SUVmax of malignant and benign lesions overlapped, but no malignant lesion showed FDG uptake ≤3.15. Asymptomatic malignant lesions were detected with a sensitivity of 100%, a negative predictive value of 100% and a specificity of 45.1%. Conclusion: Malignant transformation of PN also occurs in asymptomatic children and adolescents. Detection of MPNST at early stages could increase the possibility of oncologically curative resections.